Basements and Intersections. (4th July 2013) - Carastathis, Anna
Abstract : In this paper, I revisit Kimberlé Crenshaw's argument in "Demarginalizing the Intersection of Race and Sex" (1989) to recover a companion metaphor that has been largely forgotten in the "mainstreaming" of intersectionality in (white‐dominated) feminist theory. In addition to the now‐famous intersection metaphor, Crenshaw offers the basement metaphor to show how—by privileging monistic, mutually exclusive, and analogically constituted categories of "race" and "sex" tethered, respectively, to masculinity and whiteness—antidiscrimination law functions to reproduce social hierarchy, rather than to remedy it, denying Black women plaintiffs legal redress. I argue that in leaving the basement behind, deployments of "intersectionality" that deracinate the concept from its origins in Black feminist thought also occlude Crenshaw's account of the socio‐legal reproduction of hierarchical power.